Effects of chlorpyrifos exposure on liver inflammation and intestinal flora structure in mice. Issue 1 (25th January 2021) - Zhang, Yecui; Jia, Qiang; Hu, Chenyang; Han, Mingming; Guo, Qiming; Li, Shumin; Bo, Cunxiang; Zhang, Yu; Qi, Xuejie; Sai, Linlin; Peng, Cheng
Abstract: Chlorpyrifos (CPF) is an organophosphate insecticide commonly used to treat fruit and vegetable crops. CPF can cause severe adverse effects on body organs including the liver and central nervous system. This study investigated the CPF-induced inflammation in mice and explored the role of intestinal flora changes in liver inflammation. Adult C57BL/6 male mice were exposed to a CPF of 0.01-, 0.1-, 1- and 10-mg/kg bodyweight for 12 weeks. The mice in experimental group given CPF solution dissolved in corn oil vehicle by gavage, was administered by intraoral gavage for 5 days per week for 12 weeks. Histopathological examination and inflammatory factor detection were performed on mice liver tissue. Faeces were used for 16S ribosomal RNA high-throughput sequencing to explore the impact of CPF on intestinal flora structure and diversity. The results showed that 1- and 10-mg/kg CPF caused different degrees of liver focal inflammation. The structure of intestinal flora changed significantly in mice including the decreased beneficial bacteria (Akkermansia, Prevotella and Butyricimonas) and increased pathogenic bacteria (Helicobacter and Desulfovibrio). Meanwhile, the results of Q-RT-PCR showed that there was more total bacterial DNA in the liver tissue of the mice treated with 10-mg/kg groups. In conclusion, the imbalance of intestinal flora, the decreased abundance of beneficial bacteria and the increased abundance of pathogenic bacteria, as well as the increase of total bacterial DNA in the liver tissues, maybe associated with the liver focal inflammation induced by CPF.